The influence of linear and nonlinear pedagogy on motor skill performance: the moderating role of adaptability - Yang, Qishun; Song, MingLiang; Chen, Xiao; Li, Min; Wang, Xiaoan (Frontiers in Psychology, 2025)
This study addresses the gap in understanding the moderating role of adaptability in the effects of linear pedagogy (LP) and nonlinear pedagogy (NLP) on motor skill performance (MSP), particularly in dynamic sports environments. Recognizing the limited exploration of adaptability’s moderating role in existing literature, this research investigates how adaptability influences the effectiveness of these pedagogical strategies among college students. Forty university males students with no prior soccer experience were randomly assigned to LP or NLP groups and underwent an 8-week training program. MSP was measured by passing successful rate, and adaptability was measured as a composite indicator integrating both the variability of passing types (Variational Pass Rate) and the effectiveness of these variations (Variational Pass Success Rate). Assessments were conducted at three stages: pre-test, post-test, and a 4-week later retention-test. Results demonstrated NLP’s dual superiority: enhancing immediate passing successful rate (post-test Δ = 0.09 ± 0.045 vs. LP’s 0.06 ± 0.035, p = 0.024) and sustaining skill retention (4-week decline: NLP Δ = -0.013 ± 0.033 vs. LP Δ = −0.032 ± 0.028, p = 0.048). Crucially, adaptability significantly moderated NLP’s effectiveness during skill acquisition (pre to post: β = 0.478, R2 = 0.229, p = 0.033), explaining 22.9% of performance variance. This study not only underscores the superior benefits of NLP in fostering enduring motor skills but also highlights the pivotal role of adaptability in tailoring pedagogical approaches. These insights advocate for integrating adaptability assessments into sports education curricula to optimize training outcomes based on individual adaptability levels.